Using electron irradiation to probe iron-based superconductors. (14th May 2018) - Cho, Kyuil; Kończykowski, M; Teknowijoyo, S; Tanatar, M A; Prozorov, R
Abstract: High-energy electron irradiation at low temperatures is an efficient and controlled way to create vacancy–interstitial Frenkel pairs in a crystal lattice, thereby inducing nonmagnetic point-like scattering centers. In combination with London penetration depth and resistivity measurements, the electron irradiation was used as a phase-sensitive probe to study the superconducting order parameter in iron-based superconductors (FeSCs), lending strong support to sign-changing s ± pairing. Here, we review the key results of the effect of electron irradiation in FeSCs.